Respuesta:
Cuando y = 3 ⇒ x = 0
Cuando x = -2 ⇒ y = -1
Explicación paso a paso:
Cuando y = 3
3y = 6x + 9
3 (3) = 6x + 9
9 = 6x + 9
9 - 9 = 6x
0 = 6x
[tex]\frac{0}{6}[/tex] = x
x = 0
Cuando x = -2
3y = 6 (-2) + 9
3y = -12 + 9
3y = -3
y = [tex]\frac{-3}{3}[/tex]
y = -1
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Verified answer
Respuesta:
Cuando y = 3 ⇒ x = 0
Cuando x = -2 ⇒ y = -1
Explicación paso a paso:
Cuando y = 3
3y = 6x + 9
3 (3) = 6x + 9
9 = 6x + 9
9 - 9 = 6x
0 = 6x
[tex]\frac{0}{6}[/tex] = x
x = 0
Cuando x = -2
3y = 6x + 9
3y = 6 (-2) + 9
3y = -12 + 9
3y = -3
y = [tex]\frac{-3}{3}[/tex]
y = -1